Investigation of ignition characteristics in a kerosene fueled supersonic combustor. (August 2019) - Tian, Ye; Yang, Shunhua; Xiao, Baoguo; Zhong, Fuyu; Le, Jialing
Abstract: Ignition characteristics of a kerosene fueled supersonic combustor has been numerically and experimentally investigated in the present paper. Flame luminosity images and wall pressure measurements are used for better understanding the ignition and combustion characteristics, air throttling is used to enhance ignition in the combustor. The results are obtained under the inflow condition of Ma number 2.0, total pressure 1.0 MPa and total temperature 1100 K which corresponds to Ma4.5 flight condition. When the ER (Equivalence Ratio) of kerosene is 0.19, the kerosene cannot be ignited at all only by the spark plug. When the flux ratio of air throttling (the ratio of mass flux of air throttling to mass flux of the inflow air) is 9.1%, a small part of kerosene can be ignited, but the flame is blown off soon. When the throttling air flux ratio is increased to 13.7% or 24.5%, the kerosene can be ignited successfully, and the combustion is stable and intense. Cold room temperature liquid kerosene can be ignited successfully by the spark plug with the aid of the throttling air. Highlights: Ignition characteristics were numerically and experimentally investigated. Flame luminosity images and wall pressure measurements are used in the tests. Few published papers focused on the effects of air throttling on ignition.